Radio listeners clubs boosts climate resilience for bean farmers in Tanzania - Kiogora, Joseline; Kagabo, Desire; Byandaga, Livingstone; Mvuyibwami, Patrick; Ngige, Chris (2024)
On the sidelines of the PICSA Lite masterclass in Tanzania, FADECO Radio and Radio Huguka held a workshop in Karagwe and Kigoma (Tanzania) to establish Radio Listeners Clubs. This initiative which is facilitated by the ECREA project, aims to increase farmers' engagement and climate resilience by providing tailored weather information.